Schistosomiasis transmission; socio-demographic, knowledge and practices as transmission risk factors in pregnant women - Salawu, Oyetunde T. (J Parasit Dis, 2014)
Schistosoma transmission is influenced by the interplay between various factors ranging from parasite to host associated factors. While many studies have focused on mass chemotherapy to reduce transmission in other populations, no study has examined the impact of social factors that favour transmission in pregnant women in Nigeria. The study was conducted to assess the impact of knowledge, attitudes and sociodemographic factors on schistosomiasis burden in pregnant women of rural communities of Nigeria. A cross sectional community-based field study was conducted to assess the association between Schistosomahaematobium burden and the associated risk factors among pregnant women in rural endemic communities of Nigeria. Structured questionnaire was used to gather information on participants’ socio-demographic data, knowledge on schistosomiasis and water contact activities. Of the 237 respondents examined microscopically for infection, 50 (21.1 %) were infected with overall mean infection intensity of 69.6 ± 165.2 eggs/10 mL urine. Multivariate logistic analysis showed occupation of the women to be associated with infection with the artisans having the highest risk (OR 3.34, CI 1.67–6.69, P = 0.022). Contact with water and water usage patterns are also associated with prevalence of disease with fetching (OR 2.04, CI 0.19–3.51, P = 0.003) and multipurpose water usage (OR 4.31, CI 2.17–8.57, P = 0.0002) being the most predisposing variables respectively. Awareness about water borne diseases showed no association with infection (P = 0.382) with typhoid (23.7 %) and fever (2.6 %) constituting the most and least common water borne diseases mentioned by the women. Health education and provision of good water supply should be integrated into the control strategies in order reduce transmission in endemic areas.